Sodium-decorated P-C 3 N: A porous 2D framework for high-capacity and reversible hydrogen storage - Laranjeira, José A.S. [UNESP]; Martins, Nicolas F. [UNESP]; Lima, Kleuton A.L.; Xiao, Lingtao; Chen, Xihao; Ribeiro, Luiz A.; Sambrano, Julio R. [UNESP] (Elsevier, 2025)
The development of reversible hydrogen storage materials has become crucial for enabling carbon-neutral energy systems. Based on this, the present work investigates the hydrogen storage on the sodium-decorated P-C 3 N (Na@P-C 3 N), a porous carbon nitride monolayer recently proposed as a stable semiconductor. First-principles calculations reveal that Na atoms preferentially adsorb with an adsorption energy of −4.48 eV, effectively suppressing clusterization effects. Upon decoration, the system becomes metallic, while ab initio molecular dynamics simulations confirm the thermal stability of Na@P-C 3 N at 300 K. Hydrogen adsorption on Na@P-C 3 N occurs through weak physisorption, with energies ranging from −0.18 to −0.28 eV, and desorption temperatures between 231 and 357 K. The system can stably absorb 16 H 2 molecules per unit cell, corresponding to a gravimetric storage capacity of 9.88 wt%, surpassing the U.S. Department of Energy target. These results demonstrate that Na@P-C 3 N is a promising candidate for lightweight, stable, and reversible hydrogen storage.